Cultural and Cognitive Structure of the Omen: Epistemology, Axiology and Pragmatics - Tyshchenko, Oleh; Korolyov, Igor; Palchevska, Oleksandra (Տիգրան Մեծ)
The article presents the cognitive categorization principles in different ritual and nonritual situations. The semantics, structure and pragmatics of omens and the related cultural concepts in the archetypal world model are based on ethnosemiotic and cognitive analysis aspects, folklore pragmatics elements, and the cultural text verbal magic. The omens convey such significance for folk culture oppositions as good-evil, life-death, top-bottom, male-female, etc., as well as the connection with various traditional culture codes –action, оbject, zoomorphic, artifactual, sociomorphic, verbal and so on. As a holistic cultural and cognitive macrosign, taken in the unity of functions, conceptospheres and semantic oppositions, the omen is organized according to the principle of a situation-event cognitive cluster – action – reaction, forecast – belay, embodied in profiling a cultural prescription or taboo. As a cultural and folklore genre, the omens are based on the collective experience. They are fixed in the collective memory as a correlation of two situations (events) in causal connection (predictive – predictable) fixed by folk tradition. The primary attention is paid to the pragmatic and axiological properties of the omens, epistemological and ontological principles of their organization in the compared Slavic and non-Slavic linguistic (English) cultures.
Keywords: Philosophy of Art